Violence in the school: Is there possibility to contribute and solve it? - Dias, Carmen Lucia [UNESP]; Brumatti Jacon, Valeria Anesia; Vanni, Veronica Nogueira (Univ Nove Julho, 2019)
This article brings a reflection about the violence theme on the inside schools under the perspective of the theories evolutionary cognitive. It was aimed in this construct analyze the ways existing of the violence, its presence, increase, as well as, its manisfestation ways inside school unit walls, for this way understand and reflect about manners that can contribute with the school practices in order that these benefit with efficiency the transformation and change for a culture of peace, consequently the establishment of a more harmonious environment in the investigated context. We understand, thus, the necessity to promote the moral autonomy of the students, by means of pedagogical practices focused on moral education and to the rescue of ethical values. Fundamental, that are worked values as the dialogue and the mutual respect in the construction of an harmonious environment, where the students see these resources as the path for the resolution of conflicts and for democratic relations.
Keywords: School violence; Moral practices; Values; Moral autonomy